Factors influencing purchase intention towards green cosmetics in Malaysia - Choong, Cai Wen (2023)
This research investigates the factors that influence purchase intention towards green cosmetics in Malaysia, a rapidly growing market with increasing awareness of environmental sustainability. The study utilizes quantitative surveys to comprehensively explore the determinants affecting consumers' inclination to purchase eco-friendly cosmetic products. Drawing upon a theoretical framework grounded in the Theory of Planned Behavior (TPB), the extended Theory of Planned Behavior (ETPB), and the Technology of Acceptance (TAM), the research identifies and analyzes key factors such as attitude, subjective norms, perceived behavioral control, environmental concerns, and social media marketing.